2022
DOI: 10.3389/fpubh.2022.881074
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Online Learning, Smartphone Addiction Problems, and Psychological Symptoms in Chinese College Students After the COVID-19 Pandemic

Abstract: BackgroundSmartphone-based online education gained popularity during and after the COVID-19 pandemic. Although recent studies have highlighted the association between problematic smartphone use (PSU) and mental health symptoms, the potential role of online learning in this relationship remains unclear. This study aimed to analyze the relationships between higher education modes, PSU, and related psychological symptoms in university students.MethodsA total of 1,629 Chinese university students from five province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 60 publications
1
11
1
Order By: Relevance
“…Previous studies found that self-control regulates the correlation between PA and MPA. Factors such as negative emotions (eg, anxiety [ 69 , 70 ] and loneliness [ 71 , 72 ]) and mental toughness [ 73 , 74 ] have been shown to affect the relationship between PA and MPA. We speculate that these factors may modulate the relationship between PA and MPA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that self-control regulates the correlation between PA and MPA. Factors such as negative emotions (eg, anxiety [ 69 , 70 ] and loneliness [ 71 , 72 ]) and mental toughness [ 73 , 74 ] have been shown to affect the relationship between PA and MPA. We speculate that these factors may modulate the relationship between PA and MPA.…”
Section: Discussionmentioning
confidence: 99%
“…After the outbreak of the COVID-19 pandemic, many scholars across the globe have paid closer attention to the mental health of students who have undergone (emergency) online learning. For example, in China, the prevalence of symptoms of anxiety, depression, and stress was observed in 32.9, 31.9, and 14.6%, respectively, of university medical students ( Chang et al, 2021 ), and 25.13, 29.95, and 75.89% of university students from different majors suffered from anxiety, depression, and insomnia symptoms, respectively ( Zhang et al, 2022 ). In Poland, a total of 56 and 58% of the students from the Opole University of Technology were characterized by depression and stress symptoms, and even 18% of the participants had suicidal thoughts ( Rutkowska et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the total score of SAS-SV ranges from 10 to 60, and a higher score indicates a higher level of current problematic smartphone use (Kwon et al, 2013;Luk et al, 2018). The Chinese version of SAS-SV has been proved to be valid (Luk et al, 2018) and was widely applied in Chinese adults (Chen et al, 2017;Guo et al, 2020Guo et al, , 2021Zhang et al, 2022).…”
Section: Participants and Measuresmentioning
confidence: 99%